Curadoria de recursos educacionais digitais: uma proposta de formação docente para professores do Ensino Médio - Bezerra, Fábio Araújo (2023)
The pandemic crisis has led to intense changes in various sectors of society, and education has been no different. The main measure adopted was Emergency Remote Education (ERE) as an alternative to enable pedagogical mediation and the link between school, teacher and student. Different technological tools were then used to intensify the curation of multiple formats of Digital Educational Resources (DER) to develop the teaching and learning process. This scenario has highlighted educators' insecurities, limitations and difficulties in implementing a digital learning culture. Therefore, the general aim of this research was to investigate the experience of teachers at a full-time secondary school in terms of the curation of NETs in order to carry out training that could help them in their teaching practice in the context of digital culture. This is an exploratory study, which used a scoping review and action research as investigative procedures, constituting a qualitative-quantitative approach of an applied nature. Interviews and a questionnaire on Google Forms were used to collect data. The results showed that the curation of DER is an emerging function for the teaching practices of primary school teachers, especially when they plan their lessons taking into account the context of digital culture. On the other hand, they showed that teachers need to develop different competences in terms of curating DER, and that this requires ongoing training that recognises the importance of a new learning context that is constantly influenced by the transformations of the digital age. Among the contributions, we can highlight the development of a training programme on the curation of DER in the form of a workshop that could be useful for teacher training cells. The conclusion is that the context of education 4.0 requires teachers to be content curators and information mediators. For that, there needs to be a continuous process of teacher self-training that can broaden the understanding of the didacticpedagogical relevance of the curation of DER for high school.